2016
DOI: 10.21608/jpp.2016.46863
|View full text |Cite
|
Sign up to set email alerts
|

Response of Pea Plant (Pisum sativum L.) for Levels of Nitrogen, Rhizobium Inoculation and Spraying of Molybdenum on Growth, Green Pods, Dry Seed Yield and its Components

Abstract: The current study was carried out at Qaha Vegetable Research Farm (Qalubia Governorate), Horticulture Research Institute, Agriculture Research Center (A. R. C.), Egypt, during the two consecutive winter seasons of 2014/2015 and 2015/2016 to study the influence of different nitrogen fertilization levels i.e. 20, 35 and 50 Kg N/ fed., an inoculation of pea seeds (Pisum sativum L.) cv. Master B with compatible strain of the nodule bacteria Rhizobium leguminosarum, foliar spraying with molybdenum twice at the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…As for the effect of different treatments on white fly and aphid population attacking common bean plants under open field and green house conditions, the obtained results are in harmony with those of Ganie et al (2009) and Abdel-Aziz and Ismail (2016), in addition Chatterjee et al, (2013) who indicated that the use of inorganic fertilizers with FYM, vermicomposting and bio fertilizers reduces the whitefly incidence in tomato. The indirect effects of fertilization practices acting through changes in the nutrient composition of the crop have been reported to influence of plant resistance to many insect pests.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As for the effect of different treatments on white fly and aphid population attacking common bean plants under open field and green house conditions, the obtained results are in harmony with those of Ganie et al (2009) and Abdel-Aziz and Ismail (2016), in addition Chatterjee et al, (2013) who indicated that the use of inorganic fertilizers with FYM, vermicomposting and bio fertilizers reduces the whitefly incidence in tomato. The indirect effects of fertilization practices acting through changes in the nutrient composition of the crop have been reported to influence of plant resistance to many insect pests.…”
Section: Discussionsupporting
confidence: 86%
“…(2017) and Abou El-Hassan et al (2017). Using Rhizobium, Azotobacter and phosphorus solubilizing weather individual or combined enhanced the plant growth, flowering and yield of bean plants and save high amount of nitrogen fertilization led to increase the economic return Ganie et al (2009) and Abdel-Aziz and Ismail (2016). Common bean plants received chicken manure and NPK fertilizers gave the highest yield and using chicken manure only produced a good yield Alhrout et al (2016).…”
Section: Introductionmentioning
confidence: 99%